2012
DOI: 10.1111/bjh.12183
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin is a potent NOTCH2 transactivation inhibitor and efficiently induces apoptosis in chronic lymphocytic leukaemia (CLL) cells

Abstract: SummaryChronic lymphocytic leukaemia (CLL) cells express constitutively activated NOTCH2 in a protein kinase C (PKC)-dependent manner. The transcriptional activity of NOTCH2 correlates not only with the expression of its target gene FCER2 (CD23) but is also functionally linked with CLL cell viability. In the majority of CLL cases, DNA-bound NOTCH2 complexes are less sensitive to the c-secretase inhibitor (GSI) DAPT. Therefore, we searched for compounds that interfere with NOTCH2 signalling at the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…Moloney murine leukemia virus (M-MLV) reverse transcriptase and GoTaqPCR kits (Promega) were used for semiquantitative RT-PCR using primer sets as follows: HEY1 , forward 5′-ATACGCCTGCATTTACCAGC-3′ and reverse 5′-TCAATTGACCACTCGCACAC-3′. Primer sets for NOTCH1 , NOTCH2 , and ACTB were published elsewhere (Hubmann et al, 2013). Real-time quantitative RT-PCR (qPCR) for NOTCH2 was performed with TaqMan ® -probes (Hs01050717_m1) purchased from Applied Biosystems (Thermo Fisher Scientific, Waltham, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moloney murine leukemia virus (M-MLV) reverse transcriptase and GoTaqPCR kits (Promega) were used for semiquantitative RT-PCR using primer sets as follows: HEY1 , forward 5′-ATACGCCTGCATTTACCAGC-3′ and reverse 5′-TCAATTGACCACTCGCACAC-3′. Primer sets for NOTCH1 , NOTCH2 , and ACTB were published elsewhere (Hubmann et al, 2013). Real-time quantitative RT-PCR (qPCR) for NOTCH2 was performed with TaqMan ® -probes (Hs01050717_m1) purchased from Applied Biosystems (Thermo Fisher Scientific, Waltham, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the nuclear NOTCH2 activity might be resistant to γ-secretase inhibitors (GSI) (Das et al, 2004), a phenomenon that we have observed in the majority of CLL cases (Hubmann et al, 2010, 2013). In light of the observation that GSI are less effective in clinical studies (Andersson and Lendahl, 2014; Lee et al, 2015), we hypothesize that GSI resistance might be a widespread characteristic of NOTCH2 associated human malignancies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Emerging evidence suggests that the Notch signaling network is frequently deregulated in human B-CLL with up-regulated expression of Notch1 and Notch2 as well as their ligands Jagged1 and Jagged2 [42]. Moreover, Notch signaling inhibition by the gamma-secretase inhibitors (GSIs) and the specific Notch2 down-regulation using small interfering RNA (siRNA) could promote B-CLL cell apoptosis [38,42]. It has been also reported that Notch2 is not only overexpressed in B-CLL cells but also might be related to the failure of apoptosis-oriented treatment for this disease and deregulation of Notch2 signaling is involved in the aberrant expression of CD23 in B-CLL [39-41].…”
Section: Introductionmentioning
confidence: 99%
“…45 γ-Secretase inhibitors I apoptotic activity was associated with a reduction in NF-κB and p53 activities. Another recent study showed that γ-secretase inhibitors I induce apoptosis through at least three mechanisms: proteasome inhibition, endoplasmic reticulum stress increase, and Notch downregulation.…”
mentioning
confidence: 96%